TARI GANTAR EMPULUUQ TEMPUUQ DI DESA SEKOLAQ DARAT KABUPATEN KUTAI BARAT KALIMANTAN TIMUR - Susilawati, Susilawati (Institut Seni Indonesia Surakarta, 2024)
The Gantar Empuluuq Tempuuq Dance is one of the Gantar Dances in the Swalas Gunaq Art Studio in Sekolaq Darat Village. The formulation of the problems in this study are (1) how is the form of the Gantar Empuluuq Tempuuq. (2) how is the function of the Gantar Empuluuq Tempuuq Dance performance. The theoretical basis used to dissect the problem of form is to use the theory of Suzzane K. Langer trans. FX Widaryanto who stated that “form in the most abstract sense means the structure, articulation, the overall result of the relationship of various interrelated factors or rather the way all aspects are assembled”. Regarding form, Sumandiyo Hadi’s thoughts on the principles of motion are also used. To dissect the problem of function using the theory of Soedarsono which states, the function of dance is divided into three: 1. As a means of ritual/ceremony, 2. As a means of personal entertainment, 3. As a means of spectacle. The method used in this study is a qualitative method with an ethnoarchaeological approach through the stages of observation, data collection and data analysis. The research showed that the Gantar Empuluuq Tempuuq Dance in Sekolaq Darat Village is a group dance performed by female dancers carrying a wooden stick and a piece of bamboo. This dance consists of three parts depicting flying birds and always a group, supported by movement, music, make up, costumes and floor patterns that become one unit in the presentation. Gantar Empuluuq Tempuuq dance is a dance that is still desired in the midst of the Tonyooi Benuaq Dayak community. This dance not only has a function as a means of traditional ceremonies but also for the needs of the people of West Kutai Regency in their social life such as welcoming guests, entertainment and spectacle. Performing art, including dance, will continue to live and exist as long as they are functional and useful in people’s lives as supporters.